The economics of money, banking and financial markets - Mishkin, Frederic S.; Matthews, Kent.; Giuliodori, Massimo (Harlow, England ; Boston, [Mass.] : Pearson, 2013)
By applying an analytical framework to the patient, stepped-out development of models, Mishkin draws students into a deeper understanding of modern monetary theory, banking and policy. His combination of common sense applications with current events provides comprehensive coverage in an informal tone students appreciate.
Includes bibliographical references and index.
oif 24/06/15
Loan
Keywords: Finance; Money; Banks and banking